Entre dialogue et conflit : la poésie bilingue en guarani - Manon Naro (Caravelle)
This paper tries to understand how bilingual poetry considers relations between languages in Paraguay. In the first part, we shall introduce bilingualism’s issues and their consequences in bilingual poetry’s forms. In the second part, we shall focus on poetical discourse as dialogue’s support and developper of tensions between both languages. Finally, we shall analyze how the problematization of these linguistic relationships allows intercultural expresions that explore an anthropological and poetical thought.